2003
DOI: 10.1111/1467-6494.7106008
|View full text |Cite
|
Sign up to set email alerts
|

Effortful Control as a Personality Characteristic of Young Children: Antecedents, Correlates, and Consequences

Abstract: Effortful control, the ability to suppress a dominant response to perform a subdominant response, was assessed in 106 children during early childhood (at 22, 33, and 45 months) using multitask behavioral batteries. By 45 months, effortful control was highly longitudinally stable and coherent across tasks and thus appeared to be a traitlike characteristic of children's personality. Children who had been less intense in terms of proneness to anger and joy, and those who had been more inhibited to the unfamiliar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

39
525
6
12

Year Published

2007
2007
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 577 publications
(590 citation statements)
references
References 41 publications
39
525
6
12
Order By: Relevance
“…Thus, children who can manage their attention and behavior also may have the skills necessary to control their negative emotions, such as anxiety and anger (relevant to externalizing and separation distress) and manage to get along with others and to adhere to social standards. These findings support previous research with older children Kochanska et al, 2001;Kochanska & Knaack, 2003), and it is noteworthy that we included both positive and negative aspects of social functioning in our models.Central to the goals of this study, we also found evidence for the notion that effortful control mediates the relation between parenting and children's developmental outcomes. This pattern was found at both 18 and 30 months of age.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…Thus, children who can manage their attention and behavior also may have the skills necessary to control their negative emotions, such as anxiety and anger (relevant to externalizing and separation distress) and manage to get along with others and to adhere to social standards. These findings support previous research with older children Kochanska et al, 2001;Kochanska & Knaack, 2003), and it is noteworthy that we included both positive and negative aspects of social functioning in our models.Central to the goals of this study, we also found evidence for the notion that effortful control mediates the relation between parenting and children's developmental outcomes. This pattern was found at both 18 and 30 months of age.…”
supporting
confidence: 90%
“…Specifically, when children are low in effortful control, they are likely to exhibit negative outbursts, to behave inappropriately with peers and adults, and to behave aggressively. Consistent with these expectations, researchers have found that low effortful control is associated with and predicts behavior problems in preschool and school-aged populations Eisenberg et al, 2005;Eisenberg, Spinrad, et al, 2004;Kochanska & Knaack, 2003;Olson, Sameroff, Kerr, Lopez, & Wellman, 2005). Although the majority of work has been done with older children, Kochanska and Knaack (2003) found negative relations between effortful control at ages 22, 33, and 45 months and later externalizing problems at 73 months.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…The effortful control battery consisted of a battery of tasks developed by Kochanska, Padavich, and Koenig (1996) and Kochanska and Knaack (2003). The effortful control battery used at the 3-year visit consisted of three tasks: a snack delay, a whisper, and a lab gift.…”
Section: Methodsmentioning
confidence: 99%
“…Effortful control has been defined as the ability to suppress inappropriate behavior and perform required or appropriate behavior in response to environmental demands. Effortful control becomes increasingly important beyond the 2nd year of life, has considerable longitudinal stability, and predicts externalizing behavior problems at later ages (Eisenberg et al, 2005;Kochanska & Knaack, 2003;Kochanska, Murray, & Coy, 1997;Rothbart, Derryberry, & Posner, 1994). Internalization of rules of conduct has been defined as regulated or appropriate behavior in response to contextual demands even in the absence of surveillance (e.g., Kochanska & Aksan, 1995;Kopp, 1982;Maccoby & Martin, 1983).…”
mentioning
confidence: 99%